2021
DOI: 10.1111/jop.13220
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing pathologists evaluating PD‐L1 in head & neck squamous cell carcinoma

Abstract: Background Programmed death‐ligand 1 (PD‐L1) expression with combined positive score (CPS) ≥1 is required for administration of checkpoint inhibitor therapy in recurrent/metastatic head and neck squamous cell carcinoma (HNSCC). The 22C3 pharmDx Dako immunohistochemical assay is the one approved as companion diagnostic for pembrolizumab, but many laboratories work on other platforms and/or with other clones, and studies exploring the potential interchangeability of assays have appeared. Evidence from the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…In both studies, pathologists had received dedicated training in the assessment of CPS in HNSCC [ 15 ]. These results are strong evidence that training programs to update pathologists on new criteria to be applied for in situ biomarker evaluation are highly effective [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, pathologists had received dedicated training in the assessment of CPS in HNSCC [ 15 ]. These results are strong evidence that training programs to update pathologists on new criteria to be applied for in situ biomarker evaluation are highly effective [ 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…An accessible, reproducible, and robust IHC test for the evaluation of PD-L1 expression in terms of CPS is therefore crucial to guide therapy decisions in patients with HNSCC. However, technical and biological issues still hamper CPS assessment by pathologists in the clinical practice [ 9 , 10 ]. First, several antibody clones and platforms have been developed for the immunohistochemical analysis of PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, PD-L1 expression is mainly detected using immunohistochemical methods, and there is considerable variability with respect to the positive thresholds set by different studies, the antibody detection platforms and the detection techniques used. Recent studies have analyzed assays for evaluating PD-L1 expression, and the results demonstrated that SP263 assay tended to increase the degree of positive expression while SP142 assay tended to stain better immune cells ( 50 ). Cerbelli explored the inter-observer reliability and correlation between PD-L1 expression assays, which revealed high agreement between the 22C3 PharmDx assay and the SP263 assay, suggesting that the two antibodies are interchangeability in immunotherapy ( 51 ).…”
Section: Biomarkers Of Ici Therapeutic Efficacy Against Digestive Sys...mentioning
confidence: 99%
“…With complexities related to IVD staining performances, various scoring methods (TPS/ tumor cell population versus immune cells/total tumor area versus combined positive scoring [CPS]), and intratumor heterogeneity, many studies have shown substantial differences between pathologists’ interpretation of PD-L1 staining and resulting TPS 2 , 5 , 6 . This is not only a challenge related to NSCLC, but a difficulty amongst a multitude of cancer therapies 4 , 12 . Future refinement may lead to further improvement in prediction algorithms (based on TPS score in NSCLC and CPS in others cancer therapies 12 ) for response to checkpoint inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%